A review of Peruvian diving beetles of the genus Hydaticus Leach, 1817, with description of Hydaticus (Prodaticus) panguana sp. nov. and notes on other Neotropical species (Coleoptera: Dytiscidae) - Megna, Yoandri S.; Balke, Michael; Apenborn, Rico; Hendrich, Lars (Zootaxa, 2019)
We review the Peruvian Hydaticus Leach, 1817 (Coleoptera: Dytiscidae) and describe Hydaticus panguana sp. nov. from Huánuco Department. In the context of this work, we also provide new country records for several species: Hydaticus lateralis Laporte, 1835 (for Peru, Guyana, Venezuela, Suriname); H. xanthomelas (Brullé, 1837) (for Peru); H. subfasciatus Laporte, 1835 (for Colombia); H. fractivittis Guignot, 1951 (for Paraguay). Hydaticus riehli Wehncke, 1876 and H. verecundus Clark, 1864, described from “Cuba” and “South America”, respectively, were probably mislabelled specimens, and do not belong to the Neotropical fauna. Diagnostic characters, including illustrations of male genitalia and habitus, are presented for seven of the 11 Neotropical species, and a modified key is provided. Altogether four species of Hydaticus are now known from Peru.